Ansel Adams Easton 'Kajian Karya, Kesenimanan, dan Aspek Sosialnya' - Irwandi . (Rekam: Jurnal Fotografi, Televisi, Animasi)
The fame of an artist is sometimes recognized as a reflection of himself and his work features alone. The artist often regarded as a highly central role in efforts to achieve its reputation.The public do not realize that behind the popularity of an artist, there are a number of socio-cultural factors that also affect it. Ansel Adams is an example of how the position of an artist in the constellation of socio-cultural America. Besides having a beautiful work, technical ability and concept of good works, he is also able to put himself in a social map of his era. Discussion of Ansel Adams will be conducted by considering the workside, the capacity and roles deemed external helped push his popularity. In this perspective will be seen how the importance of social factors in maintaining the existence of an artist.